Mapping digital marketing research in social networks: A short-term bibliometric analysis (2018-2023) - Peixoto Rodriguez, Egidio; Espina-Romero, Lorena C. (Revista de Ciencias Sociales, 2024)
This study delved into the world of Digital Marketing in social networks, exploring its evolution from 2018 to April 2023 through the prism of the Scopus database. Using a quantitative methodology with a bibliometric approach, 368 documents were examined using statistical tools such as VOSviewer, RStudio and Microsoft Excel. The results paint a picture where the annual document production shows a steady decline of -3.34%, attributed to saturation, changing algorithms and mutable preferences. With the participation of 81 countries, Spain, USA, UK, India, and Indonesia emerge as prominent players, while 26 subject areas, led by Business, Computer Science and Social Sciences, top the subject matter. Documentary diversity is reflected in articles (76.36%), papers (15.22%) and reviews (3.80%). In this scenario, nine authors, including Civelek et al. (2020), Dwivedi et al. (2020), and Saura (2021), stand out. The exploration of trends took the form of a Thematic Map with specific sections, while future inquiries are oriented towards resource theory, destination marketing, social network platforms, diet advertising and social network analysis. Overall, this study not only provides insight into contemporary scientific production, but also points to fruitful directions for future research.